Potential For Development of Heritage In Pesantren As A Halal Tourism Destination In Madura With Community-Based Tourism - Dony Burhan Noor Hasan; Anik Sunariyah; Enni Endriyati (Lasigo Akademia Indonesia, 2022)
Heritage in Pesantren is a potential for halal tourism by prioritizing religious values which have not been given much attention. Madura is better known as the pesantren base which has grown rapidly from the past until now and the heritage of the pesantren is spiritual values that have grown as the civilization of the Madurese community in particular. This study aims to explore the heritage of pesantren in the Madurese community as a whole as potential development of halal tourism. While the approach used is community-based tourism to heritage boarding schools. The research technique used in this research is the observation of several heritage pesantren that have the potential to develop halal tourism in Sumenep Madura and in-depth interviews with managers and the community around the pesantren. The result showed that the lack of understanding of halal tourist destinations and the low literacy of the Madurese community as well as the limited time in research which becomes an obstacle to further tourism development. Thus, the presence of formal education has given a lot of transformation in the direction of pesantren education and has affected the availability of santri facilities.